Ligand binding to 2΄-deoxyguanosine sensing riboswitch in metabolic context. Issue 9 (23rd January 2017) - Kim, Yong-Boum; Wacker, Anna; Laer, Karl von; Rogov, Vladimir V.; Suess, Beatrix; Schwalbe, Harald
Abstract: The mfl -riboswitch is a transcriptional off-switch, which down-regulates expression of subunit β of ribonucleotide reductase in Mesoplasma florum upon 2΄-deoxyguanosine binding. We characterized binding of 2΄-deoxyguanosine to the mfl -aptamer domain (WT aptamer) and a sequence-stabilized aptamer (MT aptamer) under in vitro and 'in-cell-like' conditions by isothermal titration calorimetry (ITC) and nuclear magnetic resonance (NMR) spectroscopy. 'In-cell-like' environment was simulated by Bacillus subtilis cell extract, in which both aptamers remained sufficiently stable to detect the resonances of structural elements and ligand binding in 2D NMR experiments. Under 'in-cell-like'-environment, (i) the WT aptamer bound the endogenous metabolite guanosine and (ii) 2΄-deoxyguanosine efficiently displaced guanosine from the WT aptamer. In contrast, MT aptamer exhibited moderate binding to 2΄-deoxyguanosine and weak binding to guanosine. NMR experiments indicated that binding of guanosine was not limited to the aptamer domain of the riboswitch but also the full-length mfl -riboswitch bound guanosine, impacting on the regulation efficiency of the riboswitch and hinting that, in addition to 2΄-deoxyguanosine, guanosine plays a role in riboswitch function in vivo . Reporter gene assays in B. subtilis demonstrated the regulation capacity of the WT aptamer, whereas the MT aptamer with lower affinity to 2΄-deoxyguanosine was not able to regulate gene expression.